Ironheart. Meant to fly - Ewing, Eve L. (Marvel Worldwide, Inc., 2020)
As the superhero Ironheart, Riri Williams steps up to defeat an old enemy of Spider-Man's who takes world leaders hostage; searches for missing friend Miles Morales; and attempts to foil the plans of the evil Ten Rings with help from the Wasp, Doctor Strange, and Princess Shuri of Wakanda.